Primary granule exocytosis in human neutrophils is regulated by Rac-dependent actin remodeling - Mitchell, Troy (2008)
The actin cytoskeleton regulates exocytosis in all secretory cells. In neutrophils, Rac2 GTPase has been shown to control primary (azurophilic) granule exocytosis. Here, we propose that Rac2 is required for actin cytoskeletal remodeling to promote primary granule exocytosis. Treatment of neutrophils with low doses (≤ 10 μM) of the actin depolymerizing drugs, latrunculin B (Lat B) or cytochalasin B (CB), enhanced both formyl peptide receptor and Ca(2+) ionophore stimulated exocytosis. Higher concentrations of CB or Lat B, or stabilization of F-actin with jasplakinolide (JP) inhibited primary granule exocytosis measured as myeloperoxidase release, but did not affect secondary granule exocytosis determined by lactoferrin release. These results suggest an obligatory role for F-actin disassembly prior to primary granule exocytosis. However, lysates from secretagogue-stimulated neutrophils showed enhanced actin polymerization activity in vitro. Microscopic analysis showed that resting neutrophils contain significant cortical F-actin which was redistributed to sites of primary granule translocation when stimulated. Exocytosis and actin remodelling was highly polarized when cells were primed with CB, however, polarization was reduced by Lat B preincubation, and both polarization and exocytosis was blocked when F-actin was stabilized with JP. Treatment of cells with the small molecule Rac inhibitor, NSC23766, also inhibited actin remodelling and primary granule exocytosis induced by Lat B/fMLF or CB/fMLF, but not Ca(2+) ionophore. Therefore, we propose a role for F-actin depolymerization at the cell cortex coupled with Rac-dependent F-actin polymerization in the cell cytoplasm to promote primary granule exocytosis.